Transforming Javanese Culture-Based Character Values Through Language Literacy Practices in Elementary School - Niken Larasati; Sriyanto Sriyanto; Anang Widhi Nirwansyah; Ana Andriani; Niken Larasati; Sriyanto Sriyanto; Anang Widhi Nirwansyah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Regional culture-based character education is important for students but is weakening amidst the shifting currents of globalization. This study aims to analyze the process of transformation of Javanese cultural values through language literacy practices in elementary schools. The research method is qualitative with an ethnographic design. Participants consisted of four teachers (T1–T4) and six students (S1–S6), selected purposively who were involved in Javanese language literacy activities at an elementary school in Cilacap area. Data were collected through observation, interviews, and document analysis. Data analysis was carried out according to Spradley's ethnographic steps, namely domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. Data were validated through triangulation of techniques and sources. The results of the study show that Javanese language literacy practices in elementary schools can transform Javanese culture-based character values. Teachers use children's stories, habituation songs, counting with a variety of languages, discussions, drama, and experience-sharing activities to shape students' characters. As a result, Javanese culture-based character values can be understood cognitively and developed into concrete actions in everyday life, such as (1) an attitude of andhap asor (humility) in interactions; (2) guyup rukun(cooperation) emerges during literacy activities and other learning activities; (3) tepa selira (empathy) is manifested in caring for friends; (4) politeness in language becomes a consistent habit; (5) ewuh pakewuh(tolerance) develops into the ability to accept differences in a real way; and (6) grapyak semanak (social intimacy) is increasingly visible through more open and confident relationships. Literacy acts as an initial trigger, and the school social environment becomes a space for actualizing values. The role of teachers, schools, and all parties is needed to support character transformation through creative, holistic, and contextual literacy.